RKM Monitoring and Evaluation System in the City of Magelang: Proposed Concept - Nuryani, Ira; Primadewi, Ardhin (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Local government such as Regional Development Planning Agency (Bappeda), holds an important role in budget management. For example Bappeda of Magelang City in Jawa Tengah. However, there are still several issues related to the distribution of the budget from Bappeda of Magelang City to the community. One of the issues is related to the large number of neighborhood associations (RT) managed by Bappeda, which the total is 1032 RT. The issues create a challenge in managing, distributing, and monitoring the budget effectively and efficiently. The Government of Magelang City created an Advanced, Healthy and Happy Community Empowerment Program or commonly called Rodanya Masbagia. Therefore, a monitoring system for the implementation of Rodanya Masbagia is needed for the community so that the use of funds is in accordance with the needs of the community. This system focuses on monitoring Community Needs Plan (RKM) managed by Bappeda of Magelang City, especially in managing a budget of 30 million rupiah per year for each RT. This study uses a qualitative method, including data and information collection, analysis, and observation. The sample consists of one neighborhood from each district in Magelang City, focusing on mapping the results of monitoring and evaluating programs and budgets. Therefore, the results of this system will enable Bappeda of Magelang City to monitor and evaluate the distribution of funds for each RT, ensuring compliance with the proposed plan. The business process in the optimize of SIMASBAGIA uses the Ward and Peppard Methods. Analysis is carried out using PIECES, Value Chain Analysis and Fishbone Diagram which provides a big picture of the problem in terms of various aspects. The result of this research is a proposed information system for more optimal monitoring and evaluation.